Integrating reinforcement in digital fabrication with concrete: A review and classification framework. (May 2021) - Mechtcherine, Viktor; Buswell, Richard; Kloft, Harald; Bos, Freek P.; Hack, Norman; Wolfs, Rob; Sanjayan, Jay; Nematollahi, Behzad; Ivaniuk, Egor; Neef, Tobias
Abstract: This article offers a comprehensive, systematic overview of the existing solutions for integrating reinforcement in digital concrete technologies with particular emphasis on Additive Manufacturing (AM) with concrete, also called 3D concrete printing (3DCP). While the functionalities of various types of reinforcement are briefly addressed, the major focus is on the integration process as such, i.e., on its technological aspects. On this basis a generic classification and process description outline has been developed for reinforcement integration, which is regarded as an extension of the RILEM process classification framework for Digital Fabrication with Concrete (DFC). In many instances, the integration occurs in a separate process step prior to or after concrete shaping. This holds true for all formative digital concrete shaping processes and for many 3DCP solutions. 3DCP approaches enable, however, integration of the reinforcement during concrete shaping as part of a single-step AM process in a simultaneous or contiguous manner, while placement of reinforcement is considered to be a sub-process.